PMO-066 Salvage of occluded central venous catheters in long term parenteral nutrition patients: techniques & outcomes. (28th May 2012) - Major, G A D; Small, M; Gabe, S M
Abstract : Introduction: Central venous catheter (CVC) occlusion is a recognised complication of parenteral nutrition (PN). Various techniques are advocated to salvage the CVC but forcing debris from fibrin or precipitate into the bloodstream risks causing catheter-related bloodstream infection (CRBSI) or embolism. We decided to assess the efficacy of simple physical techniques to salvage an occluded CVC, and the rate of complications described. Methods: All CVC occlusions between January 2010 and December 2011 were reviewed. Occlusions were "total", when the CVC could not be flushed, or "partial", when there was resistance to flushing. The cause of occlusion was recorded together with the time from symptom onset to attempted salvage, age of the CVC, techniques and instillations used to unblock the CVC, and outcomes. Confirmed cases of CRBSI occurring within 30 days of CVC salvage were recorded. Techniques included: manipulation of the external segment of the CVC to disrupt visible material (M); saline flush of the CVC with a gentle, pulsing action using a 2.5 ml Luer lock syringe for 20–60 min (SF); instillation of alcohol to dissolve lipid (A); pulsed flushing of urokinase without instillation (U); physical clearing out of the CVC hub with a 21G needle to remove any obstructing material (HC). Results: 38 occlusions occurred in 23 patients giving an occlusion rate of 10.9% (0.25 occlusions/1000 catheter days): 11 partial occlusions in five patients and 27 total occlusions in 19 patients. See Abstract PMO-066 table 1 below: The rate of CRBSI in this group was 0.02 CRBSI/1000 catheter days in the 2-year period assessed. This compares with a rate in patients not suffering occlusions of 0.91 CRBSI/1000 catheter days. Conclusion: CVC salvage is often possible with line manipulation and persistent pulsatile flushing. Hub clearout with a needle is also safe and effective. Alcohol and urokinase have an occasional role but are often not required and may not work without additional measures. Post-salvage complications are rare. The apparent negative association between occlusion and infection runs contrary to the belief that infection and occlusion are linked, and warrants further study. Competing interests: None declared.